Gideon & Otto - Dunrea, Olivier (Boston : Houghton Mifflin Harcourt, 2012)
Otto the toy octopus goes everywhere with Gideon, a small gosling, but while Gideon is playing with some rabbits Otto falls off the wall on which he was left and makes a new acquaintance
Accelerated Reader
Accelerated Reader 1.2
Keywords: Geese -- Juvenile fiction; Toys -- Juvenile fiction; Rabbits -- Juvenile fiction; Geese -- Fiction; Toys -- Fiction; Rabbits -- Fiction; Geese -- Fiction; Toys -- Fiction; Rabbits -- Fiction; Series; picture books; Picture books